GEOLOGICAL AND GEOCHEMICAL PECULIARITIES AND AGE OF RAPAKIVI-LIKE GRANITES OF THE EASTERN HOVSGOL REGION - Reznitsky L.Z.; Belichenko V.G.; Barash I.G.; Sandimirova G.P.; Pakhol'chenko Yu.A. (My University, 2003)
Specific porphyraceous biotite-amphibole granites considered rapakivi-like according to texture and rock and mineral compositions have been distinguished among granitoids in the eastern Hovsgol region. The granites are close in geochemistry to the A-2 subtype of A-granites. According to structure, geochemical characteristics, and the absence of superposed structural and metamorphic alterations, the rapakivi-like granites are classified as postorogenic. Rb-Sr isochron dating of five bulk-rock samples yields the age of 423.4±20.3 Ma (MWSD = 0.217) at (87Sr/86Sr)0 - 0.7069. Mineral isochron yields the age of 402.6±4.5 Ma (MWSD = 2.31) at Sr0 = 0.7067, which coincides within the experimental error with the date obtained from the bulk-rock isochron. These dates correspond to the time of the closure of Rb-Sr systems during the cooling of the granite massif, which crystallized (intruded) somewhat earlier. The data obtained indicate that folding and metamorphic processes in the eastern Hovsgol region terminated by the early-middle Silurian. Taking into account the time gap between the intrusion of postcollision granites and collision processes, regional metamorphism in the eastern Hovsgol region might have occurred synchronously with high-grade metamorphism in the southern Baikal area (480-490 Ma). This supports the correct recognition of the Khamar-Daban metamorphic terrane comprising zonal metamorphic complexes of the eastern Hovsgol and central and western Khamar-Daban regions and the Slyudyanka granulite complex in the southern Baikal area.
Keywords: Rapakivi-like granites; geochemistry; Rb-Sr age; eastern Hovsgol region; Paleozoic::Silurian; Палеозой::Силурийская